1998
DOI: 10.1046/j.1365-2885.1998.00114.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic disposition and arthropathic potential of oral ofloxacin in dogs

Abstract: We examined the relation between the pharmacokinetic disposition and arthropathic potential of ofloxacin, a new quinolone antibacterial agent, using both male immature (3-month-old) and mature (18-month-old) beagles. Ofloxacin was orally administered to these dogs at 20 mg/kg once daily for 8 consecutive days, and the animals were killed 2 h after the last treatment. Serum ofloxacin concentrations were repeatedly measured on days 1 and 7 by use of high-performance liquid chromatography (HPLC), and pharmacokine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 24 publications
2
23
0
1
Order By: Relevance
“…Meanwhile, the pharmacokinetic analysis revealed a linear relationship between absorption following oral administration and tissue distribution. Ofloxacin concentrations in sera and articular cartilages obtained in the 20 mg/ kg/day group were also compatible with those of the previous report [23]. At the non-arthropathic dose (5 mg/kg/ day), the C max , AUC 0-24 and articular cartilage concentrations were 3.4 µg/ml, 35.1 µg⋅hr/ml and 7.0 µg/g, respectively.…”
Section: Disscusionsupporting
confidence: 91%
See 4 more Smart Citations
“…Meanwhile, the pharmacokinetic analysis revealed a linear relationship between absorption following oral administration and tissue distribution. Ofloxacin concentrations in sera and articular cartilages obtained in the 20 mg/ kg/day group were also compatible with those of the previous report [23]. At the non-arthropathic dose (5 mg/kg/ day), the C max , AUC 0-24 and articular cartilage concentrations were 3.4 µg/ml, 35.1 µg⋅hr/ml and 7.0 µg/g, respectively.…”
Section: Disscusionsupporting
confidence: 91%
“…In our previous report [23], the arthropathic lesion due to ofloxacin was observed only in juvenile dogs, despite the fact that the drug concentration in the synovial fluid and articular cartilage of immature dogs (3-month-old) was equal to or lower than those in mature dogs (18-month-old). Kato and coworkers [10] have indicated that metabolically active immature chondrocytes are more sensitive to the effects of a quinolone, compared with inactive mature cells in the ex vivo study using 3 H-thymidine.…”
mentioning
confidence: 72%
See 3 more Smart Citations